A systematic review and meta-analysis of observational evidence for the use of bailout self-expandable stents following failed anterior circulation stroke thrombectomy. (10th November 2018) - Wareham, James; Flood, Richard; Phan, Kevin; Crossley, Robert; Mortimer, Alex
Abstract : Background: The crucial role of thrombectomy in the management of emergent large vessel occlusive stroke is not disputed but there is a technical failure rate in a significant minority of patients whose outcomes are often poor. Our objective was to perform a systematic review and meta-analysis to assess the safety and efficacy of permanent self-expandable stent deployment as a bailout procedure in cases of failed anterior circulation thrombectomy. Methods: Two independent reviewers searched the Pubmed (Medline) database for studies reporting outcomes following failed endovascular thrombectomy with subsequent rescue therapy employing self-expandable stents. Results: Eight studies (one prospective, seven retrospective) originating from Europe, Asia, and America comprising 160 patients met the inclusion criteria. Estimated baseline National Institutes of Health Stroke Scale score was 17.1 (95% CI 15.7 to 18.4). Following failed thrombetcomy and stent deployment, the rate of favorable outcome (modified Rankin Scale score 0–2) was 43% (95% CI 34% to 53%). Pooled mortality was 21% (95% CI 13% to 33%). Successful recanalization (Thrombolysis in Cerebral Infarction (TICI) 2b–3 or Thrombolysis in Myocardial Infarction (TIMI) 2–3) was 71% (95% CI 63% to 77%). Symptomatic intracerebral hemorrhage was seen in 12% (95% CI 7% to 18%). The Solitaire stent (Medtronic) was the most commonly deployed stent following failed thrombectomy attempts (66%; 95% CI 31% to 89%). Pre- or post-stent angioplasty was performed in 39%of patients (95% CI 29% to 48%). Glycoprotein IIb/IIIa inhibitors were used in 89% (95% CI 71% to 97%). 95% of patients received postprocedural antiplatelet therapy. Conclusion: A rescue stent procedure seems reasonable as a last resort following failed thrombectomy but currently the level of evidence is limited. Prospective registries may aid in guiding future recommendations.